TB KNOWLEDGE AND PERCEPTION IN PAKISTAN - Jamal Abdul Nasir; Muhammad Imran; Syed Arif Ahmed Zaidi (Journal of University Medical & Dental College, 2016)
ABSTRACT BACKGROUND: The main idea of the study to explore the socio demographic factors that have association with TB knowledge, perception and its cure. METHODS: Bivariate and binary logistic regression analysis have been carried out by using the Pakistan demographic and health survey 2012-13 of ever married men age 15-49. RESULTS: Higher proportion of the respondents heard about TB and believed that TB is a curable infectious disease. More than half (57%) of the respondents pronounced that Tuberculosis spread by air through coughing or sneezing. Binary logistic analysis revealed that respondents with no education has sufﬁcient lack of knowledge about TB [OR=0.191]as compared to their counterpart having higher educational degree. Respondents watching TV have more prone to know about TB [OR=2.942] compared to those have no access to TV. Respondents belong to Sindh, Punjab and KPK 4.75, 3.89 and 3.62 times more knowledge about TB respectively as compared to those lived in GB. CONCLUSION: Age, education place of residence, media access particularly TV and wealth index are found to be signiﬁcant regarding TB knowledge and its cure. These statistical outcomes can be emerging in TB management and control.